Micronanostructured Design of Dendrite‐Free Zinc Anodes and Their Applications in Aqueous Zinc‐Based Rechargeable Batteries. Issue 6 (23rd March 2021) - Cui, Bing-Feng; Han, Xiao-Peng; Hu, Wen-Bin
Abstract : Aqueous zinc‐based rechargeable batteries are considered to be one of the most promising new energy storage systems due to their unique advantages (e.g., low cost, high safety, environmental friendliness, and high energy density). However, the formation of zinc dendrites at the anode during the operation can puncture the separator and even cause short circuit of batteries, which is one of the serious problems in Zn‐based batteries. Therefore, understanding the growth process of dendrites and suppressing the formation of zinc dendrites are necessary for the further development and large‐scale applications of Zn‐based batteries. Herein, the growth mechanism and the influence factors of zinc dendrites are first introduced in detail by combining the experimental and theoretical results. Moreover, the effective strategies for suppressing dendrites through micronanostructured design are summarized, including surface modification, alloying, and substrate selection/porous structure engineering. In the end, the challenges in the further development of high‐performance dendrite‐free zinc anode are discussed, and the research frontiers trends are prospected as well. It is aimed to shed light on the rational design and structure tuning of high‐performance zinc electrode materials for advanced zinc‐based secondary batteries for clean energy storage technologies. Abstract : Developing highly stable and reversible zinc anode materials is critical to improve the electrochemical performance of zinc‐based batteries. Herein, the recent progress on micronanostructured strategies for dendrite‐free zinc anode and their applications in aqueous rechargeable batteries is provided. Current challenges and future directions are proposed to give guidance for the further development of high‐performance zinc‐based electrode materials.